2015
DOI: 10.1002/cjp2.31
|View full text |Cite
|
Sign up to set email alerts
|

The infiltration, and prognostic importance, of Th1 lymphocytes vary in molecular subgroups of colorectal cancer

Abstract: Giving strong prognostic information, T‐cell infiltration is on the verge of becoming an additional component in the routine clinical setting for classification of colorectal cancer (CRC). With a view to further improving the tools for prognostic evaluation, we have studied how Th1 lymphocyte infiltration correlates with prognosis not only by quantity, but also by subsite, within CRCs with different molecular characteristics (microsatellite instability, CpG island methylator phenotype status, and BRAF and KRAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 48 publications
2
36
0
1
Order By: Relevance
“…Furthermore, Ling et al reported the favorable prognostic impact of Tbet+ TILs in MSI CRC, and observed the same trend (not statistically significant however) in MSS CRC. 40 Thus, our results demonstrate that quantification of Tbet+ can recapitulate the favorable ongoing IFNγ response induced by Th1/Tc1 TILs, more frequent in MSI but also in some "inflamed" MSS CRC. To further characterize these "inflamed" MSS CRC, especially the potential immunogenicity of BRAF or RAS mutations in those tumors, we correlated the Tbet/CD3 ratio with the tumor BRAF or RAS mutational status but did not find any significant difference between mutated or wild-type MSS CRC.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Furthermore, Ling et al reported the favorable prognostic impact of Tbet+ TILs in MSI CRC, and observed the same trend (not statistically significant however) in MSS CRC. 40 Thus, our results demonstrate that quantification of Tbet+ can recapitulate the favorable ongoing IFNγ response induced by Th1/Tc1 TILs, more frequent in MSI but also in some "inflamed" MSS CRC. To further characterize these "inflamed" MSS CRC, especially the potential immunogenicity of BRAF or RAS mutations in those tumors, we correlated the Tbet/CD3 ratio with the tumor BRAF or RAS mutational status but did not find any significant difference between mutated or wild-type MSS CRC.…”
Section: Discussionsupporting
confidence: 51%
“…The identification of Tbet+ TILs by immunohistochemistry was previously reported in CRC in only few studies, with a higher density in MSI than in MSS CRC in line with our results. 39,40 However, these studies did not precise the heterogeneous expression of this biomarker, especially among MSS CRC between inflammatory versus noninflammatory tumors, a major issue in this therapeutic and prognostic context. Furthermore, Ling et al reported the favorable prognostic impact of Tbet+ TILs in MSI CRC, and observed the same trend (not statistically significant however) in MSS CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,41 Lymphovascular invasion was recorded as present or absent (yes or no). Tumor budding at the invasive front was quantified on pancytokeratin-stained slides according to Prall et al 42 and scored as low grade (0-9 buds per microscopic field) or high grade (10 or more), adapted from Ueno et al 43 Infiltration of different subsets of lymphocytes and macrophages has also previously been assessed in the CRUMS cohort, 5,6,41,44 along with infiltration of neutrophils (CD66b C ) (unpublished evaluation). After exclusions due to unavailable or insufficient tumor sample, and/or lack of clinical information, 436 patients were included in the study.…”
Section: Study Populationmentioning
confidence: 99%
“…Several studies, by us and others, have focused on the tumor immune response which has proven critical to prognosis in CRC. [2][3][4][5][6][7] Findings in this area have driven the design of the Immunoscore system, 8 which is to be implemented in clinic as a complement to the TNM staging system.…”
Section: Introductionmentioning
confidence: 99%